Renal tubular epithelial cell necroptosis promotes tubulointerstitial fibrosis in patients with chronic kidney disease. Issue 12 (4th November 2022) - Lin, Ziyan; Chen, Ai; Cui, Hongwang; Shang, Ruihua; Su, Tian; Li, Xiaoyan; Wang, Kekun; Yang, Jing; Gao, Keli; Lv, Jie; Shen, Jie; Wang, Shanzhi; et al.
Abstract: Renal fibrosis, a common pathological manifestation of virtually all types of chronic kidney disease (CKD), ultimately predisposes patients to end‐stage renal disease. However, there is no effective therapy for renal fibrosis. Our earlier studies proved that RIP3‐mediated necroptosis might be an important mode of renal tubular cell death in rats with chronic renal injury. Under transmission electron microscopy (TEM), we found morphological changes in the necrosis of human renal tissue, and the percentage of necrotic cells increased significantly in patients with stages 2 and 3a CKD. Immunofluorescence analyses showed that the percentages of TUNEL + /RIP3 + double‐positive and TUNEL + /MLKL + double‐positive tubular epithelial cells in renal tubules of patients with stages 2 and 3a CKD were significantly increased compared to those in control patients without renal disease. Immunohistochemistry analyses of renal biopsy specimens from patients with CKD revealed RIP3, MLKL, and p‐MLKL upregulation in patients with stages 2 and 3a CKD, suggesting that necroptosis of renal tubular epithelial cells in CKD patients occurs, and the peak of necroptosis was in stages 2 and 3a CKD. We showed that profibrotic factor proteins (TGF‐β1, Smad2 and Smad3) and fibroblast activation markers (α‐SMA and Vimentin) were specifically upregulated in stage 2 and 3a CKD patients. In addition, Pearson correlation analysis showed that the percentage of necroptotic renal tubular epithelial cells was positively correlated with TGF‐β1 and collagen‐I. We also showed that RIP1/3 or MLKL inhibitors decreased the expression of RIP3, MLKL, TGF‐β1, and Smad3 in HK‐2 cells treated with TNF‐α. FGF‐2, α‐SMA, Vimentin and FN were overexpressed in the hRIFs cultured with the supernatant of necroptotic HK‐2 cells, whereas necroptosis blockers (Nec‐1s, GSK'872 and NSA) and TGF‐β1/Smad3 pathway antagonists (LY364947 and SIS3) reduced FGF‐2, α‐SMA, Vimentin and FN levels. Collectively, necroptosis of renal tubular epithelial cells in CKD patients occurs, and the peak of necroptosis was in stages 2 and 3a CKD. Renal tubular epithelial cell necroptosis mediates renal tubulointerstitial fibrosis in patients with chronic kidney disease, which is related to the TGF‐β1/Smad3 signaling pathway.